Test of Vibrations Influence on the Measurement Accuracy in the Precise Digital Leveller Trimble Dini 03 And Comparison of its Vibration Sensitivity with Leveller Ni 002 - Kurnatowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents findings from research on the effect of vibrations on the accuracy of measurement with an automatic precise digital leveller. A special research station was created to induce vibrations on a leveller and to measure vibration parameters that affect staff reading. It contains description of discovered relationship between the vibration parameters and the mean error of a single height difference measurement.
Keywords: vibrations; measurement accuracy; precise levelling; leveller digital; drgania; dokładność pomiaru; poziomowanie; niwelator cyfrowy